Optimization of cylindrical shells subjected to pitting corrosion - Pochtman, Yuriy M.; Fridman, Mark M. (Computer Assisted Methods in Engineering and Science, 2023)
The paper presents modelling of optimization process of thin-walled structures such as vertical cylindrical reservoirs subjected to pitting corrosion. The problem is formulated in terms of nonlinear mathematical programming. The function which is a product of its constituents is accepted as the optimization criterion. The choice of an optimal thickness of the reservoir shell along the height is determined from the conditions of its equal reliability.